PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN DALAM PEREDARAN MINUMAN BERALKOHOL DI KOTA PEKANBARU (STUDI DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU) - Andriansyah Andriansyah; Ahmad Tarmizi Yussa (UIR Press, 2017)
Protection to the circulation of consumption goods already regulated by government which there is a institution or department which handle about industrial and commercial. One of the task of the institution is supervising the goods that are consumed by society. In this case, there are some consumption goods such as foods and baverages like junkfood, in packing and bottle. One of baverage is supervised by Industrial and Commercial Department is aperatif. In Pekanbaru, aperitif sales necessary orderly which aims to protect the society from aperitif. Based on Peraturan Menteri Perdagangan Nomor 20 Tahun 2014, as the kinds of aperitif products which may merchantability approriate with its place, such as types A, B, and C. The aims of this research are identifying and explaining about supervision circulation of aperitif by Industrial and Commercial Department in Pekanbaru. To knowing obstacle factors in supervising of aperitif by Industrial and Commercial Department in Pekanbaru. Phenomenon that shows lack of supervision conducted by Industrial and Commercial Department in circulation of aperitif, as much circulation of aperitif which is not approriate its place. Still a lot of aperitif sales above 5% are sold independently in society. There are some shops or stalls which sell aperitif that not use a license as by the government. This research use qualitative method. Head of Trade from Industrial and Commercial Department of Pekanbaru as key informant and seller of aperitif as informant. Data collection respondent was done by conducting interviews with informant. Documentation and observation was conducted to see the results of Supervision of Idustrialand Commercial Department in Distribution of Aperitif in Pekanbaru A Case Study at Marpoyan District, Pekanbaru.